Scaling Biodiversity Conservation Efforts: An Examination of the Relationship Between Global Biodiversity Targets and Local Plans - Pierce, Jennifer Rae; Drill, Sabrina; Halder, Michael D.; Tan, Mika Mei Jia; Tiwari, Anushri; López Guijosa, Pablo A. (Frontiers in Conservation Science, 2021)
Cities have a critical role to play in meeting global-scale biodiversity targets. Urban socio-ecological systems connect human and ecological well-being. Their outsized impact reaches well beyond their geographic borders through cultural, ecological, and economic interactions. Although cities account for just 2% of the earth’s surface, they host over half of the human population and are responsible for 75% of consumption. The Parties to the Convention on Biological Diversity (CBD) and others have acknowledged the important role cities can play in achieving global targets. In response, at least 110 cities have produced plans focused on biodiversity, but we do not know the extent to which these city plans align with global targets or what role they play in achieving these targets. Here, we explore the relationship between global biodiversity conservation targets and local biodiversity plans to identify how elements at the two scales align or diverge. We compared the CBD Strategic Plan 2011–2020 (Aichi Targets) with 44 local biodiversity plans (often called LBSAPs) from multiple major world regions. We analyzed more than 2,800 objectives, actions, outputs, and indicators extracted from the local plans to measure the relationship with these global targets. Our results show how local approaches to biodiversity conservation can inform post-2020 global frameworks to improve coordination between global and local scale processes. We identify actions particular to the local scale that are critical to conserve global biodiversity and suggest a framework for improved coordination between actors at different scales that address their respective roles and spheres of influence.